The use of passive acoustics to observe the presence and movement of pygmy blue whales (balaenoptera musculus brevicauda) in the Perth Canyon, WA - Gavrilov, Alexander; McCauley, Robert; Pattiaratchi, C.; Bondarenko, O. (2012)
Understanding the distribution and movements of whales is a challenging task: these animals move fast, dive deep and generally don’t spend a lot of time at the surface or close to the shore where they can be visually observed. Acoustic methods can offer some advantages over traditional visual surveys and satellite tracking methods as these can be time consuming and costly. Passive acoustic methods are based on recordings of whale vocalizations and can collect data over long periods of time regardless of weather conditions. Pygmy blue whales (Balaenoptera musculus brevicauda) are subspecies of the blue whales (Balaenoptera musculus) which are regarded as endangered on the IUCN Red List. The migration routes of both pygmy blue whales and true blue whales are largely unknown [1], however the population of the pygmy blue whales visiting Perth Canyon is believed to spend their summer south of 52°S [2] and then migrate along the WA coast towards Indonesia. The Perth Canyon off Western Australia is the largest (100km long) and deepest (4000 meters) submarine canyon in Australia. Pygmy blue whales are known to use the Perth Canyon as a staging area on their northern migratory leg and aggregate primarily in a small area of perhaps 5 x 10 nautical miles at the Canyon Head, which is believed to be their feeding ground [3, 4]. A passive acoustic observatory was deployed at the edge of the Perth Canyon in Western Australia in 2008 as part of the Australian Integrated Marine Observing System (IMOS). The observatory consists of four autonomous sea noise recorders set on the seafloor as a triangular array of about 5-km sides with the fourth recorder placed near the centre of the array. The recorders are recovered every eight months to retrieve sea noise data and then redeployed for another period of data collection, so that passive acoustic observations in the Perth Canyon area are almost uninterrupted. Pygmy blue whales produce songs consisting of regular and repeated sounds. The most common song recorded in the Perth Canyon consists of three-sound themes which lasts for approximately 120 seconds [5]. Results of detection and tracking of vocalizing pygmy blue whales from the IMOS acoustic observatory during the deployment period from November 2009 to July 2010 are considered in this article.